1996
DOI: 10.1097/00007890-199608150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Combined Foscarnet-Ganciclovir Treatment for Cytomegalovirus Infections After Allogeneic Hemopoietic Stem Cell Transplantation1

Abstract: In a previous study, we showed that patients undergoing allogeneic hemopoietic stem cell transplantation (HSCT) who had cytomegalovirus (CMV) antigenemia with more than 4 CMV antigen-positive cells/200,000 have a high transplant-related mortality (TRM) rate, despite treatment with ganciclovir or foscarnet. In an attempt to reduce TRM, 32 allogeneic HSCT recipients, between the ages of 16 and 55 years (median, 35 years), with CMV antigenemia (> or = 5 positive cells) developing at a median interval from HSCT of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 12 publications
1
52
0
Order By: Relevance
“…Combination ganciclovir and foscarnet therapy has been utilized in AIDS patients with retinitis 20 and in allogeneic stem cell recipients. 21 Recent work suggests that a combination of reduced-dose ganciclovir and foscarnet may be effective and less toxic for ganciclovir-resistant CMV in solid organ transplant recipients. 22 Cidofovir, the third FDA-approved drug for the treatment of CMV, 23 has been used primarily for retinitis in AIDS patients and for CMV in allogeneic stem cell recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Combination ganciclovir and foscarnet therapy has been utilized in AIDS patients with retinitis 20 and in allogeneic stem cell recipients. 21 Recent work suggests that a combination of reduced-dose ganciclovir and foscarnet may be effective and less toxic for ganciclovir-resistant CMV in solid organ transplant recipients. 22 Cidofovir, the third FDA-approved drug for the treatment of CMV, 23 has been used primarily for retinitis in AIDS patients and for CMV in allogeneic stem cell recipients.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] In the future, initial pre-emptive therapy with this combination might be considered in patients with prolonged immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study including a preponderance of sibling BMT patients has shown that CMV infection-guided treatment gives the same outcome as prophylactic GCV. 23 Future possible strategies might include alternative methods of GVHD prophylaxis, 24 suppression of CMV infection with foscarnet 25,26 or a combination of foscarnet and GCV, 27 continuing GCV prophylaxis for longer to prevent late CMV disease, adoptive transfer of CD8 + CMV-specific CTL clones derived from the marrow donor, 28 or enhancing immune reconstitution post BMT by the use of subunit anti-CMV vaccines such as gB or pp65. 29,30 …”
Section: Discussionmentioning
confidence: 99%